Vol.2 - Tisdell, Clem (New Delhi, 2007)
Despite rapid economic progress and pledges by the developed nations to eliminate poverty, millions of people still remain in poverty globally. Most of the poverty-stricken, but not all, live in developing countries. Those who continue to be in poverty have been unable to share in the benefits of global economic growth. This shameful situation, one in which poverty persists amongst global plenty, has resulted in the United Nations declaring poverty reduction, with the ultimate aim of eliminating poverty, to be its major goal for the 21st century. Consequently, this book, Poverty, Poverty Alleviation and Social Disadvantage, provides a relevant and timely worldwide coverage and analysis of the occurrence of poverty, of policies for its alleviation, and of issues involving social disadvantage. Social disadvantage usually accompanies poverty. Most contributions to this book are interdisciplinary in character, even though economic aspects predominate. This book, after providing new general perspectives on poverty and social disadvantage and policies to address those, follows up by presenting a wide range of original national and regional studies, including some in-depth unique case studies of situations involving poverty and social disadvantage. The relative coverage of topics in this book broadly reflects the comparative geographical incidence of poverty globally. A feature of this book is that the contributions have been written by experts who have first-hand knowledge of the social issues they address.
Keywords: Poverty